Survey of indoor fungi of sick patients Al-Diwania hospital and evaluated efficiency of sterile materials - et.al, Majedkadem AL-Shably (Al-Qadisiyah Journal of Pure Science, 2017)
The study included 200 samples of air corridors of hospital patients in the education of Diwaniyah during the study period, namely, (11/01/2011 to 04/30/2012). The results showed that 123 samples showed growth of fungal and by 61.1% of the air corridors of patients, where they were diagnosed 8 races innate is the genus Aspergillus, who took the lead a number isolates are 44 isolation were distributed among five types of the Aspergillus flavus 19 isolates (15.4)% and Aspergillus niger 18 isolates (14.6)% Aspergillus candidus 3 isolates (2.4)% and 2 isolates each of Aspergillusfumigatus and Aspergillusterreus (1.6)% sex Penicillium sp 28 isolates (22.7)% and genus Mucor sp 26 isolates (21.1)%, and was diagnosed 2 isolates each race of races following Alternariaalternata and Rhizopus sp and Candida albicans and Cryptococcus neoformans (1.6)%, either the results of the sensitivity of fungi to cleansers formalin and Dettol that the percentage of inhibition of these compounds for the fungus differentiated by the type and concentration of disinfectant, sex and type innate this was the disinfectants in the concentrations original 10% in the most efficient inhibition of fungi than if used in diluted concentrations of 5% and 2.5% formalin was more effective on fungi and yeasts of Dettol.